The Worldwide Spread of the Tiger Mosquito as Revealed by Mitogenome Haplogroup Diversity - Battaglia, Vincenza; Gabrieli, Paolo; Brandini, Stefania; Capodiferro, Marco R.; Javier, Pio A.; Chen, Xiao-Guang; Achilli, Alessandro; Semino, Ornella; Gomulski, Ludvik M.; Malacrida, Anna R.; Gasperi, Giuliano; Torroni, Antonio; et al. (Frontiers in Genetics, 2016)
In the last 40 years, the Asian tiger mosquito Aedes albopictus, indigenous to East Asia, has colonized every continent except Antarctica. Its spread is a major public health concern, given that this species is a competent vector for numerous arboviruses, including those causing dengue, chikungunya, West Nile and the recently emerged Zika fever. To acquire more information on the ancestral source(s) of adventive populations and the overall diffusion process from its native range, we analyzed the mitogenome variation of 27 individuals from representative populations of Asia, the Americas and Europe. Phylogenetic analyses revealed five haplogroups in Asia, but population surveys appear to indicate that only three of these (A1a1, A1a2 and A1b) were involved in the recent worldwide spread. We also found out that a derived lineage (A1a1a1) within A1a1, which is now common in Italy, most likely arose in North America from an ancestral Japanese source. These different genetic sources now coexist in many of the recently colonized areas, thus probably creating novel genomic combinations which might be one of the causes of the apparently growing ability of Ae. albopictus to expand its geographical range.